Laboratory Evaluation of a Bioacoustic Bubble Strobe Light Barrier for Reducing Walleye Escapement. (15th September 2014) - Flammang, Mark K.; Weber, Michael J.; Thul, Megan D.
Abstract: Fish escapement is a largely overlooked challenge to managing reservoir fisheries. Physical barriers may help retain fish in reservoirs but are often not practical due to high reservoir debris loads and maintenance requirements of these structures. As an alternative, nonphysical barriers may also be successful at increasing fish retention in reservoirs through the use of negative stimuli that divert fish away from targeted locations. However, the effectiveness of nonphysical barriers can vary considerably among barrier stimuli and fish species because the barrier's success is dependent upon on a behavioral response from fish. We conducted a laboratory experiment to evaluate the effectiveness of a bioacoustic bubble–strobe light barrier at reducing Walleye Sander vitreus escapement rates. We hypothesized that increasing the number and frequency of barrier stimuli would result in Walleyes approaching the barrier less frequently, reduced escapement, and increased amount of time before escapement occurred. Walleyes approached the barrier and were successfully deterred most often when lights were off and sound was on. Walleye escapement rates declined from 89.3% with the barrier off to 44.1% with low and medium sound, whereas up to 100% of the fish escaped with the addition of light. Mean time before escapement and time to 50% escapement increased with the use of sound, whereas fish escaped in less time when light was used as a deterrent. Most Walleyes escaped around sunset indicating that fish were most active during the crepuscular period. Despite reductions in escapement associated with sound–bubble barriers, we recommend that alternative nonphysical barriers be evaluated for their potential to further increase retention of Walleyes before installation of sound barrier deterrent systems in reservoirs. Received December 23, 2013; accepted June 27, 2014